The Influence of Non-Investment Variables on Total Asset Growth: Multiple Regression Analysis in Sharia Insurance Using Classical Assumption Tests - Ferdiansyah Ferdiansyah; M. Yuda Pratama; Aditia Saputra; Fadhlul Mubarak (Sean Institute, 2026)
This study investigates the influence of Receivables and Acquisition Costs on the asset growth of Islamic insurance companies in Indonesia. The research emphasizes how receivables management and customer acquisition expenditures contribute to strengthening financial performance. The novelty of this study lies in simplifying the regression model by excluding variables that cause multicollinearity, thereby producing a more reliable model. Unlike previous studies that broadly examined asset-related variables, this research highlights Receivables and Acquisition Costs as the primary determinants of asset growth. A quantitative approach was employed using secondary data from financial statements, analyzed through multiple linear regression with R software, and validated using classical assumption tests. The findings reveal that Receivables have a positive and significant effect on asset growth, underscoring their role as a dominant factor in enhancing financial stability. Conversely, Acquisition Costs show a positive but insignificant effect, indicating limited contribution to asset expansion. The second regression model proved more reliable than the initial model, as it met all classical assumptions. This study is limited to the Islamic insurance sector in Indonesia, restricting generalization. The implications suggest that firms should prioritize receivables management as a core strategy, while regulators such as the Financial Services Authority (OJK) should strengthen oversight of receivable-based asset quality. Future research is recommended to incorporate additional variables, including investment activities and macroeconomic factors, to provide a more comprehensive understanding of asset growth determinants.